2014
DOI: 10.1080/00032719.2014.961606
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Heavy Metals in Water and Tissues of Crucian Carp (Carassius auratus Gibelio) Collected from Subsidence Pools in Huainan Coal Fields (China)

Abstract: Heavy metals are an important class of chemical contaminants and food is a major vehicle for entry into the ecosystem. Crucian carp (Carassius auratus Gibelio) is an aquatic organism affected by metals and constitutes a major source of contaminated food in the subsidence area. Therefore, cadmium, copper, lead, and zinc were determined in the water of subsidence pools and different tissues of Carassius auratus Gibelio. In addition, the metal concentrations in water and fish from this study were compared with na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 60 publications
0
5
0
Order By: Relevance
“…Essential elements (Cu and Zn) are accumulated higher in the tissue organs compared to the non-essential elements (Cd, Pb, Hg, and As). Many researchers have observed a similar accumulation pattern of higher concentration of essential elements in the tissue organs compared to the non-essential elements (Zubcov et al 2012;Wang, Chu, et al 2015;Varol et al 2017;Anandkumar et al 2018). Among the analyzed metals in the fish species, Cu, Zn, and Cd show higher concentration in the viscera tissue; Cr, Pb, Hg and As shows higher accumulation in muscle tissue and Mn accumulated higher in the gill tissue, whereas in bivalve species accumulation of Cu, Zn, Mn, Pb, Hg and As was higher in gill tissues; Cr and Cd show higher accumulation in gonad tissue.…”
Section: Accumulation Of Elements In Various Tissue Organsmentioning
confidence: 77%
See 1 more Smart Citation
“…Essential elements (Cu and Zn) are accumulated higher in the tissue organs compared to the non-essential elements (Cd, Pb, Hg, and As). Many researchers have observed a similar accumulation pattern of higher concentration of essential elements in the tissue organs compared to the non-essential elements (Zubcov et al 2012;Wang, Chu, et al 2015;Varol et al 2017;Anandkumar et al 2018). Among the analyzed metals in the fish species, Cu, Zn, and Cd show higher concentration in the viscera tissue; Cr, Pb, Hg and As shows higher accumulation in muscle tissue and Mn accumulated higher in the gill tissue, whereas in bivalve species accumulation of Cu, Zn, Mn, Pb, Hg and As was higher in gill tissues; Cr and Cd show higher accumulation in gonad tissue.…”
Section: Accumulation Of Elements In Various Tissue Organsmentioning
confidence: 77%
“…Muscle tissue is commonly considered as the organ with the low accumulation ability for toxic metals. However, this is not always the case, previous studies by Liu et al (2015) and Jia et al (2017) have reported the higher concentration of non-essential elements (Cr, As and Cd) in the muscle tissue of S. fuscescens, P. fulvidraco and C. carassius compared to gill and liver tissues. This can be due to the distinct circulation pattern of heavy metals between various fish species (Liu et al 2015).…”
Section: Accumulation Of Elements In Various Tissue Organsmentioning
confidence: 88%
“…The content of manganese in the muscles of fish from Lake Kenon is lower than that presented in the work (Rahman et al 2012), which might be due to the tendency of various species of fish to concentrate certain elements in their tissue more than the surrounding. In the food components of the fish stomach in Lake Kenon, the high concentration of Zn, Mn and Hg shows that chemical contaminants enter organisms not only through the environment but also with food, which is supported by research (Wang et al 2015). For example, it was detected that approximately 70% of methylated Hg is consumed with food, while only 10% is accumulated through gills (Heath 2002).…”
Section: Chemical Elements Distribution In Fish Muscles and Food Components Of The Fish Stomachmentioning
confidence: 77%
“…Mn was related with Zn in the subsidence pond with a pillaring photovoltaic cover (p ≤ 0.05). Usually, the positive correlations between the heavy metals are most likely related to their common source [27]. Therefore, Cr, Ni, and Cu had the same origin in different subsidence ponds.…”
Section: Heavy Metals Source Analysis In Different Subsidence Pondsmentioning
confidence: 99%